Analysis of patient referrals to the outpatient haematology clinic in Elbląg - Zaucha, Jan; Adamowicz, Krzysztof; Zalewska, Marta; Zabłocka, Aleksandra; Adamowicz, Joanna; Mital, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2011)
Waiting time for a haematology consultation in Poland ranges from a couple to several dozen weeks. This is due to the shortage of haematology specialists, their uneven distribution and lack of clear rules regarding patient referrals to outpatient haematology clinics (OHCs). Complete blood count (CBC) is a cheap and widely performed laboratory test. However, in view of problems frequently encountered by primary care physicians with proper interpretation of CBC results, particularly with the differential diagnosis of malignant blood diseases from benign or reactive abnormalities, we hypothesized that the main reason for referring patients to OHCs might be any CBC deviation. To test this hypothesis, we analysed the structure of patient referrals to the OHC in Elbląg. Additionally, we sought to establish guidelines for primary care physicians to follow while referring patients identified with CBC abnormalities for haematology assessment. The study analyses the reasons for 986 patient referrals to the OHC in Elblag (in 2005-2009). Referrals due to CBC abnormalities were also evaluated to determine their severity. Most of the patients (690) referred to the OHC were female (70%). The most common reason for OHC referral, identified in 33% of patients with CBC abnormalities, was anaemia, followed by thrombocytopenia (25%) and leucopenia (16%). The severity of CBC abnormalities was mild in the majority of patients. At the time of their first OHC visit, only 60% of anaemia and thrombocytopenia cases in fact met the criteria for the respective diagnosis, which indicates that the abnormalities resolved spontaneously and could have been monitored by the primary care physician. Based on the above results and own experience, the authors have proposed practical guidelines on referral indications in the case of CBC abnormalities. The guidelines, coupled with the expansion of knowledge of haematological diseases among primary care physicians, might contribute to reducing the number of patients referred for haematology assessment.